2008
DOI: 10.1038/ncb1780
|View full text |Cite
|
Sign up to set email alerts
|

The type I TGF-β receptor engages TRAF6 to activate TAK1 in a receptor kinase-independent manner

Abstract: Transforming growth factor-beta (TGF-beta) is a multifunctional cytokine that regulates embryonic development and tissue homeostasis; however, aberrations of its activity occur in cancer. TGF-beta signals through its Type II and Type I receptors (TbetaRII and TbetaRI) causing phosphorylation of Smad proteins. TGF-beta-associated kinase 1 (TAK1), a member of the mitogen-activated protein kinase kinase kinase (MAPKKK) family, was originally identified as an effector of TGF-beta-induced p38 activation. However, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
510
3
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 496 publications
(543 citation statements)
references
References 27 publications
28
510
3
2
Order By: Relevance
“…The TRAF6-TAK1-JNK/p38 pathway is essential in TGF-β induced apoptosis in prostate cancer cells. [19] This pathway also depends on SMAD7 as a scaffolding protein, enabling activation of p38. [20] R-SMAD-dependent pathways are also involved in apoptosis and one important regulator of apoptosis, the tumor suppressor gene Other mechanisms by which I-SMADs regulate SMAD signaling include prevention of R-SMAD/SMAD4 heteromerization by binding to SMAD4, recruitment of SMURFs to receptors leading to receptor degradation, and direct inhibition of transcriptional responses.…”
Section: Tgf-β/bmp Induced Apoptosismentioning
confidence: 99%
“…The TRAF6-TAK1-JNK/p38 pathway is essential in TGF-β induced apoptosis in prostate cancer cells. [19] This pathway also depends on SMAD7 as a scaffolding protein, enabling activation of p38. [20] R-SMAD-dependent pathways are also involved in apoptosis and one important regulator of apoptosis, the tumor suppressor gene Other mechanisms by which I-SMADs regulate SMAD signaling include prevention of R-SMAD/SMAD4 heteromerization by binding to SMAD4, recruitment of SMURFs to receptors leading to receptor degradation, and direct inhibition of transcriptional responses.…”
Section: Tgf-β/bmp Induced Apoptosismentioning
confidence: 99%
“…Mouse anti-Flag (M2, 1:5,000), rabbit anti-Flag (1:5,000) and anti-β-actin (1:5,000) antibodies were obtained from Sigma. Ubiquitination assays of endogenous or ectopically expressed MyD88 were performed as described [43][44][45] with minor modifications. Cells were transfected with the indicated plasmid, and subsequently treated with TGF-β1 in certain conditions.…”
Section: Construction Of Small Hairpin Rnas and Lentiviral Infectionmentioning
confidence: 99%
“…In this process, TAK1-associated binding protein-2 (TAB2) acts as a bridge linking TRAF6 to TAK1 [26]. Although the mechanism by which TAK1 is activated is not fully understood, many studies have revealed the critical role of the lysine-63-linked polyubiquitination by TRAF6 in the activation of TAK1 [27,28].…”
Section: Introductionmentioning
confidence: 99%